Diffusion-weighted image versus contrast-enhanced kinetic curves: which is more valuable in assessment of breast cancer? - Salma A.A.N Abokhozayem; Hosnia A Mohammed; Sally M Osama (Wolters Kluwer Medknow Publications, 2022)
Background and aim Noninvasive radiological techniques such as dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) can help distinguish between malignant and benign lesions of the breast. The current study was conducted to evaluate the diagnostic values of DCE-MRI and DWI in differentiation between benign and malignant breast lesions. Patients and methods This study was conducted on 30 patients with 32 lesions during the period from June 2019 to May 2020 at the Radiology Department and approved by the Ethics Committee. DCE-MRI and DWI were acquired for each patient using a 1.5 T machine with breast coils. Histopathological results were collected as a gold standard of the study. Results Of 32 lesions, histopathology revealed that 22 (68.75%) lesions were malignant and 10 (31.25%) lesions were benign. Mean apparent diffusion coefficient (ADC) of benign lesions was 1.25±0.56×10−3 mm2/s, which was significantly higher than those of malignant lesions (0.93±0.42×10−3 mm2/s). DWI-MRI had high sensitivity, specificity, positive predictive value, negative predictive value, and accuracy in distinguishing benign from malignant lesions (90.9, 70, 86.96, 77.78, and 84.38%, respectively). However, the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of DCE-MRI were 95.5, 80, 91.3, 88.9, and 90.6%, respectively. Conclusion Compared with DWI, DCE-MRI has a higher sensitivity and specificity for distinguishing between benign and malignant lesions of the breast. Diffusion-weighted MRI provides quantitative assessment of benign and malignant lesions of the breast by measuring the ADC values.